Phylogenetic appraisal of the genus Platoma (Nemastomatales, Rhodophyta), including life history and morphological observations on P. cyclocolpum from the Azores - Gabriel, Daniela (2013)
IV European Phycological Meeting”, Oviedo, Espanha, 22-27 de julho de 2007. [Poster communication].